(untitled) (Nepal Medical College Journal, 2025)
Occurrence of cardiovascular accidents inside a dental office is not a surprising event given the stress many patients associate with dental care. Upon graduating from dental school as a dental practitioner, students must be prepared to deliver appropriate measures promptly for successful management of cardiac emergencies occurring in dental clinic. However, there are no documented studies on such preparedness in Nepal yet. Thus, an institutional based cross-sectional study was conducted from June-August 2025 among dental students in Kathmandu, Nepal to assess their level of knowledge, attitude and practice on management of cardiovascular medical emergencies plus it’s variation based on age, gender and different academic levels of study. A pre-validated close-ended questionnaire consisting of 22 questions was used to assess the study parameters. Statistical analysis was conducted using the chi-square test and binomial regression. Regarding knowledge assessment, significant gaps were identified in several topics. Out of 138 participants, over half (53.6%) were still confused regarding the CPR (cardio-pulmonary resuscitation) procedure, only 21.7% knew the common cause of cardiac arrest in children and 25.4% understood the functional capacity assessment using metabolic equivalent tasks (METs). About half of the students (52.2%) favored cardio-cerebral resuscitation (CCR) over traditional CPR procedure, with 4th year students showing significantly more positive attitudes (66.7%) compared to interns (41.3%) (p=0.015). Age group and gender were not significant predictors of attitude towards CCR. Only, 44.2% of the students expressed willingness to perform mouth-to-mouth resuscitation on unconscious patients. The practice assessment revealed concerning gaps in emergency preparedness and experience. Only 5.8% of students had encountered cardiac emergencies in clinical settings and merely 11.6% had participated in mock emergency drills. A minority (14.5%) felt capable of managing code blue situations, with interns showing higher confidence (28.3%) compared to 4th year students (2.6%) (p=0.008). However, there was significant variation in continuing education participation, with 4th year students showing higher engagement (66.7%) compared to postgraduate students (29.4%) (p=0.028). Expertise in management of cardiovascular medical emergencies is essential for dental students who will eventually become dental health-care professionals. They have a critical need for clinical exposure and training in managing such situations.